2019
DOI: 10.7717/peerj.7591
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotional state slows down movement speed: behavioral and neural evidence

Abstract: Background Athletic performance is affected by emotional state. Athletes may underperform in competition due to poor emotion regulation. Movement speed plays an important role in many competition events. Flexible control of movement speed is critical for effective athletic performance. Although behavioral evidence showed that negative emotion can influence movement speed, the nature of the relationship remains controversial. Thus, the present study investigated how negative emotion affects movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…1 and 2. This trend is also confirmed in several previous studies (Li, Zhang, Zhou, & Wang, 2019; Zhang et al, 2020). In the existing toolboxes, for example, Dien’s PCA Toolkit (Dien, 2010a) and Kayser’s erpPCA (Kayser & Tenke, 2003), the scales (i.e., polarity and amplitude) of these PCA-extracted components are poorly considered so that these components cannot be directly analysed simultaneously when their scales are different.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…1 and 2. This trend is also confirmed in several previous studies (Li, Zhang, Zhou, & Wang, 2019; Zhang et al, 2020). In the existing toolboxes, for example, Dien’s PCA Toolkit (Dien, 2010a) and Kayser’s erpPCA (Kayser & Tenke, 2003), the scales (i.e., polarity and amplitude) of these PCA-extracted components are poorly considered so that these components cannot be directly analysed simultaneously when their scales are different.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…[20] Biomotor speed and flexibility are essential components in karate. In a competition, speed and flexibility have an important role to get effective movement in athletes [24]. From the results of measurements made on the 50-meter sprint test, it was found that athletes were divided into 3 categories, consisting of perfect, excellent, and good.…”
Section: Discusionmentioning
confidence: 99%
“…The Self-Assessment Manikin Scale is a scale that measures emotional domains such as valence, arousal, and dominance (Bradley & Lang, 1994). Because this scale is effective and is of low cost, it has been widely used in the study of emotions (Bynion & Feldner 2017;Geethanjali et al, 2017;Li et al, 2019;Murdoch et al, 2019). This study focused on the element of valence, which is an element that refers to the internal emotional dimension that is positive (attraction) or negative (rejection) triggered by something, whether it is an object or not an object.…”
Section: Self-assessment Manikin Scalementioning
confidence: 99%